Dual-chambered venous access port as alternative access for extracorporeal apheresis therapy. Issue 2 (March 2021) - Michell, Hans; Nezami, Nariman; Morris, Christopher; Hong, Kelvin
Purpose: To evaluate the use of a dual-chambered venous access port for extracorporeal apheresis therapy. Methods: This was a single-center retrospective analysis of all patients who received a dual-chambered venous access port for apheresis therapy over a 36-month period. Clinical success was defined as successful completion of at least one round of apheresis via the venous access port. Major complications were defined as any event requiring elevation of patient care and/or venous access port removal or repositioning. Minor complications were defined as venous access port issues resolved with clinical intervention. Results: Forty-four patients had a venous access port placed at the time of this study. Patients underwent red cell exchange (n = 33), therapeutic plasma exchange (n = 6) or extracorporeal photopheresis (n = 5). Forty (90%) patients had autoimmune diseases and four (10%) had neoplastic processes. Clinical success was achieved in 42 (95.5%) patients. Average venous access port dwell time was 632 days (range = 42–1191 days). All therapies through the venous access ports were well tolerated and no patients reported pain or discomfort. Major complications were seen in nine (20.5%) patients–the majority (n = 7) of which were due to venous access port malfunction–and resolved with catheter revision. One (2.27%) major complication involved an infected venous access port, and one involved a large hematoma at the venous access port site. Minor complications were seen in eight (18.2%) patients, where simple flushing of the catheter with saline or tissue plasminogen activator resolved the issue. Conclusion: The dual-chambered venous access port was successfully used for sustained blood flow in apheresis therapy with a moderate, yet correctable complication rate.